Letter (copy) : International Solidarity Fund - Tewson, Vincent
030-0207-001 HVT/FC/EK/528. Secretary's. 7th February, 1938. Mr. W. Schevenels, The International Federation of Trade Unions, 9, Avenue d'Orsay, Paris, VIIe. Dear Mr. Schevenels, INTERNATIONAL SOLIDARITY FUND I thought you might be interested in some notes which I have received from Mrs. Adams de Puertas, particularly the one where she very favourably comments on the work of the International Solidarity Fund. I also enclose copy of a letter which I have sent to her in order that there should be no misunderstanding in regard to the question of reports. Yours sincerely, Assistant Secretary. Notes. Copy of letter. 292/946/30/207